Productive Waqf Paradox: How Misconceptions lead to the Wrong Practices - Ahmad Rodzi Pawanteh; Rubai Ahmad Munawar; Sudin Haron (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
Productive waqf has become one of the latest topics of interest among Islamic economics researchers. They believe that this mechanism is truly significant, yielding noble outcomes that benefit both this world and the hereafter. Initially, there were three types of waqf: religious waqf, philanthropic waqf, and posterity (or family) waqf. Currently, scholars and researchers are inclined to discuss waqf from an economic perspective. They believe that this new dimension of waqf is far superior to other elements in the Islamic economic system. Unfortunately, those wishing to jump onto the bandwagon of this trending topic often create confusion and mislead public understanding regarding this truly significant mechanism. There is a concern that history might repeat itself, echoing the trajectory of the Islamic banking system, where the original philosophy was hijacked by those imbued with the conventional system, ultimately replacing the original religious foundation with a profitability motive. This paper provides a detailed review of the true meaning of productive waqf, its nature, and the differences between various kinds of waqf. We also offer our professional opinions on ensuring the sustainable prosperity of this kind of waqf. Hopefully, this paper will serve as a guideline for those who wish to establish a productive waqf that serves the benefits of the Muslim community.